Implementasi PermenPANRB Nomor 7 Tahun 2026 dalam Penguatan Peran Pengawas Sekolah sebagai Penjamin Mutu Pendidikan - Yusup Sangroni; Farid Syarifudin; Naeli Fajriyah; Slamet Abdun Nafi; Erni Fatmawati; Arif Kusworo (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the implementation of the Regulation of the Minister of Administrative and Bureaucratic Reform (PermenPANRB) Number 7 of 2026 in strengthening the role of school supervisors as quality assurance agents in education. This research employed a descriptive qualitative approach conducted at MI Islamiyah 02 Rakit Banjarnegara, MI Islamiyah Senting Boyolali, MI Muhammadiyah 01 Merden Banjarnegara, MIS Miftahul Afkar Bumiayu Brebes, MI NU Banat Kudus, and MI Al Huda Mangli Pemalang. Data were collected through observation, semi-structured interviews, and documentation. The findings indicate that the implementation of PermenPANRB Number 7 of 2026 is carried out through the preparation of supervisory programs based on the needs of educational institutions, the implementation of academic and managerial supervision, assistance in curriculum implementation, teacher mentoring within professional learning communities, and data-based evaluation of quality improvement programs. This policy strengthens the role of school supervisors as professional mentors, facilitators of reflective practice, and strategic partners for madrasah principals and teachers in improving the quality of learning. Supporting factors for the implementation include the commitment of madrasah principals, active teacher participation, a strong school quality culture, and effective coordination between school supervisors and the madrasah community. The challenges identified include limited time for supervision, the heavy workload of school supervisors, the large number of supervised educational institutions, differences in school characteristics, and limited technology- and data-based supporting facilities.(PermenPANRB) Number 7 of 2026, School Supervisors, Quality Assurance, Academic Supervision, Educational Quality